2014
DOI: 10.1103/physrevb.89.155307
|View full text |Cite
|
Sign up to set email alerts
|

Combined study of microwave-power/linear-polarization dependence of the microwave-radiation-induced magnetoresistance oscillations in GaAs/AlGaAs devices

Abstract: We report the results of a combined microwave polarization-dependence-and power-dependence study of the microwave radiation-induced magnetoresistance oscillations in high mobility GaAs/AlGaAs heterostructure devices at liquid helium temperatures. The diagonal resistance was measured with the magnetic field fixed at the extrema of the radiation-induced magnetoresistance oscillations, as the microwave power was varied at a number of microwave polarization angles. The results indicate a non-linear relation betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Regarding the microwave power dependence and linear polarization dependence of RiMOs, previous studies 8,10,23,37,40,41 have also drawn the conclusion that at the magnetic fields corresponding to the extrema of RiMOs, the R xx varies nonlinearly with P and the extremal R xx follows R xx (θ) = A ± Ccos 2 (θ − θ 0 ) at low P . Regarding the polarization dependent distortion from cosine square function at high microwave power range, one must consider power and polarization angle together.…”
Section: (G) To (I) That the Amplitude Ofmentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding the microwave power dependence and linear polarization dependence of RiMOs, previous studies 8,10,23,37,40,41 have also drawn the conclusion that at the magnetic fields corresponding to the extrema of RiMOs, the R xx varies nonlinearly with P and the extremal R xx follows R xx (θ) = A ± Ccos 2 (θ − θ 0 ) at low P . Regarding the polarization dependent distortion from cosine square function at high microwave power range, one must consider power and polarization angle together.…”
Section: (G) To (I) That the Amplitude Ofmentioning
confidence: 98%
“…For the power dependence, there has been a debate whether the amplitude of RiMOs increases linearly with the microwave power as indicated by the inelastic model 30 . Here, some experimental work 8,20,23 and the radiation driven electron orbital model 37 have suggested that the RiMOs amplitude actually increases sublinearly in the microwave power. So far as the role of microwave polarization in RiMOs is concerned, the inelastic model 30 and experiment 15 indicated that RiMOs are independent of the polarization angle of linearly polarized microwave, while another set of experiments 9,10 and theory, i.e, the displacement model 40 and the radiation driven electron orbital model 41 , suggested that the RiMO amplitude depends on the polarization angle of linearly polarized microwave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…. The linear-polarizationsensitivity of these oscillations has been a topic of intensive recent experimental study [13,17,23,26,28,34,35]; these studies have shown that the amplitude of microwave radiation-induced magnetoresistance oscillations changes periodically with the linear microwave polarization angle.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that over the last few years important experimental [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and theoretical efforts [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] have been made on MIRO and ZRS, their physical origin still remains controversial and far from reaching a definite consensus among the people devoted to this field. For instance, the two, in principle, accepted theoretical models explaining MIRO, (displacement [31] and inelastic [35] models) are under question in regards of recent (and even older) experimental results [43,44] that they are not able to explain. In fact, experimentalists on MIRO are calling for other theoretical approaches that might be more successful offering solid arguments on MIRO and ZRS physical origin [26,27,32].…”
mentioning
confidence: 99%